Development of an ELISA procedure to study sorption of atrazine onto a sewage sludge-amended luvisol soil - Lima, D. L. D.
Pesticides may contaminate ground and surface waters and one of the major factors governing this property is soil sorption. Sorption can be assessed by batch equilibrium technique which produces lots of extracts with high dissolved organic carbon concentration in which the pesticide concentration has to be determined. We developed an ELISA procedure to analyse atrazine based on polyclonal antibodies (C193) for which tracer structure and dilutions of immunochemical reagents were adapted to fit the purpose. After a 1000-fold dilution (or after an SPE clean-up procedure) extracts of a sewage-sludge amended luvisol (used as an example application of the methodology developed) could be reliably analysed. The Freundlich model is able to describe adsorption for this system (r(2) = 0.977) delivering a distribution coefficient K(F) of 1.6 +/- 0.2 (mg kg(-1)) (mg L(-1))(-N) and an isotherm nonlinearity factor N of 0.70 +/- 0.09. (C) 2011 Elsevier B.V. All rights reserved.